Performance-based seismic design of RC frame structure with energy dissipative cladding panel connection system using equivalent energy design procedure. (1st November 2022) - Xie, Linlin; Sha, Huiling; Chong, Xun; Hou, Linbing; Guo, Yufei
Abstract: Recently, a high-performance reinforced concrete (RC) frame structure with an energy dissipative cladding panel connection system (EDCPCS) was proposed. It creatively uses the relative deformation between the main structure and the cladding panel through U-shaped steel dampers (USDs) to dissipate plastic energy and control the damage to the RC frame. To realize a performance-based seismic design of this novel structure, performance objectives of the entire structure, USDs, and the frame structure under four earthquake levels were recommended. Subsequently, an equivalent energy design procedure (EEDP) was developed to realize the four-level performance objectives, and a calculation method for the critical design parameters (i.e., energy modification factors) was recommended. To validate the reliability of EEDP, an eight-story structure was designed, and nonlinear time history analyses were conducted under four earthquake levels. The critical seismic responses of the overall structure, energy dissipation characteristics of the USDs, and damage characteristics of the main structure were evaluated. The results indicate that the expected performance was successfully achieved using this method, thus validating the feasibility and reliability of this method. This study provides a practical design method for RC frame structures with EDCPCS. Highlights: Four-level seismic performance objectives were recommended for the new structure. A performance-based design method was proposed by improving equivalent energy design procedure. The calculation method for critical energy modification factors were proposed. The reliability of this method was validated by a case study. The expected seismic performance under four levels of earthquake was realized.